Drug Discovery Summit: 11th Swiss Course on Medicinal Chemistry. Issue 3 (14th January 2015) - Frei, Priska; Navarra, Giulio; Sager, Christoph P.; Silbermann, Marleen; Varga, Norbert; Wamhoff, Eike‐Christian
<x xml:space="preserve">Abstract</x> A summit amongst the summits: The 11th Swiss Course on Medicinal Chemistry was held in October 2014, again in the scenic setting of the Alps in Leysin, Switzerland. One hundred participants, mostly from industry, experienced a week of expert talks about numerous aspects of drug discovery and medicinal chemistry. In this conference report, we briefly summarize the essential topics of this event, while the most inspiring lectures are described in greater detail.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>